Replication Study of “Visual Fixation on the Thorax Predicts Bystander Breathing Detection in Simulated Out-of-Hospital Cardiac Arrest” - Marco Pedrotti (International Journal of First Aid Education)
Background: Early cardiopulmonary resuscitation (CPR) by lay responders is associated with improved survival from Out-of-Hospital Cardiac Arrest (OHCA). Recognition of OHCA, i.e., a victim who is unresponsive and not breathing, is essential to begin CPR as soon as possible. In 2022, we published a simulation study (Study 1; n = 96)which found that instructing lay responders to look at chest movement enables them to detect breathing. To expand the evidence and available data on this topic, we attempted a replication (Study 2; n= 73).Methods: Participants equipped with an eye tracker entered a room where a manikin, randomly set as breathing or unbreathing, lying on the floor. After the first simulation (pre-allocation), participants were randomly allocated to a video debriefing intervention with(experimental group) or without (control group) their recorded gaze overlay, in which they reviewed their thorax examination behavior. After debriefing, the simulation was repeated (post-allocation). The main outcome was success in detecting breathing.Results: Study 2 was underpowered and failed to support the findings of Study 1. Pooling together the results of the two studies (n = 170) supports the findings of Study 1: Success rate at post-allocation did not differ between the experimental (83%) and the control group (80%), but it significantly increased from pre-allocation (65%) to post-allocation (81%; χ2 = 10.88,p < .001). Each second spent examining the thorax increased the odds of success by 16% (OR = 1.16, 95% CI,1.04-1.29). Median diagnosis time was 17.9 seconds (range = 2-119 seconds).Conclusions: Educating lay responders on how to look for chest movement enhances breathing detection performance.Contexte: La réanimation cardio-pulmonaire (RCP) pratiquée précocement par des témoins est associée à une amélioration des chances de survie en cas d'arrêt cardiaque extrahospitalier (OHCA). Il est essentiel de reconnaître l'OHCA, c'est-à-dire une victime inconsciente et qui ne respire pas, afin de commencer la RCP le plus tôt possible. En 2022, nous avons publié une étude de simulation (Étude 1 ; n = 96) qui a montré que le fait d'enseigner aux témoins à observer les mouvements du thorax leur permet de détecter la respiration. Afin d'élargir les preuves et les données disponibles à ce sujet, nous avons tenté de répliquer cette étude (Étude 2 ; n = 73).Méthodes: Les participants équipés d'un eye tracker sont entrés dans une pièce où un mannequin - dont la respiration ou son absence avait été choisie au hasard - était allongé sur le sol. Après la première simulation (pré-allocation), les participants ont été répartis de manière aléatoire entre une intervention de débriefing vidéo avec (groupe expérimental) ou sans (groupe contrôle) la surimpression de leur regard, au cours de laquelle ils ont revu leur comportement d’examen du thorax. Après le débriefing, la simulation a été répétée (post-allocation). Le outcome principal était la détection de la respiration.Résultats: L'Étude 2 manquait de puissance et n'a pas permis de confirmer les résultats de l'Étude 1. La mise en commun des résultats des deux études (n = 170) confirme les conclusions de l'étude 1 : le taux de réussite à la post-allocation ne diffère pas entre le groupe expérimental (83 %) et le groupe contrôle (80 %), mais il augmente de manière significative entre la pré-allocation (65 %) et la post-allocation (81 % ; χ2 = 10,88, p < .001). Chaque seconde passée à examiner le thorax augmentait les chances de succès de 16 % (OR = 1,16, IC 95 %, 1,04-1,29). La durée médiane du diagnostic était de 17,9 secondes (intervalle = 2-119 secondes).Conclusions: Former les témoins à observer les mouvements du thorax améliore la détection de la respiration.Usuli: uhamshaji wa mapema wa mfumo wa moyo na mapafu (CPR) unaofanywa na watu wa kwanza unahusishwa na maisha bora kutoka kwa shambulio la Moyo yanayotokea Nje ya Hospitali (OHCA). Utambuzi wa OHCA, yaani, majeruhi aliyepoteza fahamu na hapumui, ni muhimu kuanza CPR haraka iwezekanavyo. Mnamo mwaka wa 2022, tulichapisha utafiti wa maigizo (Utafiti 1; n = 96) ambao uligundua kuwa watoa huduma kuangalia mwenendo wa kifua ili waweze kugundua majeruhi anapumua. Ili kupanua ushahidi na data inayopatikana juu ya mada hii, tulijaribu kurudia (Utafiti wa 2; n = 73).Mbinu: Washiriki waliokuwa na kifaa cha kufuatilia macho walipoingia kwenye chumba ambamo midoli – iliyowekwa nasibu kama ya kupumua au isiyopumua – iliyokalazwa sakafuni. Baada ya uigizaji wa kwanza (mgao wa awali), washiriki waligawiwa kwa nasibu kwa uingiliaji wa mazungumzo ya video na (kikundi cha majaribio) au bila (kikundi cha kudhibiti) safu yao ya macho iliyorekodiwa, ambayo walikagua tabia yao ya uchunguzi wa kifua. Baada ya mazungumzo, jaribio ilirudiwa (baada ya ugawaji). Matokeo makuu yalikuwa ni mafanikio katika kugundua upumuaji.Matokeo: Utafiti wa 2 haukuwa na uwezo wa kutosha na haukuweza kuunga mkono matokeo ya Utafiti wa 1. Kuunganisha pamoja matokeo ya tafiti mbili (n = 170) kunaunga mkono matokeo ya Utafiti wa 1: Kiwango cha kufaulu katika mgao wa baada ya kugawa hakikutofautiana kati ya majaribio (83 %) na kikundi cha udhibiti (80%), lakini iliongezeka kwa kiasi kikubwa kutoka kwa mgao wa awali (65%) hadi baada ya mgao (81%; χ2 = 10.88, p < .001). Kila sekunde iliyotumiwa kuchunguza kifua iliongeza uwezekano wa kufaulu kwa 16% (OR = 1.16, 95% CI, 1.04-1.29). Muda wa utambuzi wa wastani ulikuwa sekunde 17.9 (safa = sekunde 2-119).Hitimisho: Kuelimisha watoahuduma juu ya jinsi ya kuangalia harakati za kifua huongeza utendaji wa kutambua upumuaji.Maneno Muhimu: kurudiwa, shambulio la moyo nje ya hospitali, kuiga, kupumua, kuamsha moyo na mapafu, harakati za macho.